The Influence of sociocultural differences on the process of adaptation of foreign students in the USSR/Russia - C. . Ichaka (Вестник Северо-Кавказского федерального университета, 2022)
The article focuses on the impact that socio-cultural differences had on the social adjustment of foreign students through their years of attending universities in the USSR/Russia. The empirical basis for the study comprises interviews with natives of the Republic of Mali who graduated from Soviet/Russian universities. The article offers recommendations on optimizing the social adjustment of African students coming to study in Russia.